Differential Levels of Cecal Colonization by Salmonella Enteritidis in Chickens Triggers Distinct Immune Kinome Profiles - Swaggerty, Christina L.; Kogut, Michael H.; He, Haiqi; Genovese, Kenneth J.; Johnson, Casey; Arsenault, Ryan J. (Frontiers in Veterinary Science, 2017)
Salmonella enterica serovar Enteritidis are facultative intracellular bacteria that cause disease in numerous species. Salmonella-related infections originating from poultry and/or poultry products are a major cause of human foodborne illness with S. Enteritidis the leading cause worldwide. Despite the importance of Salmonella to human health and chickens being a reservoir, little is known of the response to infection within the chicken gastrointestinal tract. Using chicken-specific kinome immune peptide arrays we compared a detailed kinomic analysis of the chicken jejunal immune response in a single line of birds with high and low Salmonella loads. Four-d-old chicks were challenged with S. Enteritidis (105cfu) and cecal content and a section of jejunum collected at three times: early (4-7 days post-infection [dpi]), middle (10-17 dpi), and late (24-37 dpi). Salmonella colonization was enumerated and birds with the highest (n=4) and lowest (n=4) loads at each time were selected for kinomic analyses. Key biological processes associated with lower loads of Salmonella clustered around immune responses including: cell surface receptor signaling pathway, positive regulation of cellular processes, defense response, innate immune response, regulation of immune response, immune system process, and regulation of signaling. Further evaluation showed specific pathways including chemokine, Jak-Stat, MAPK, and T cell receptor signaling pathways were also associated with increased resistance. Collectively, these findings demonstrate it is possible to identify key mechanisms and pathways that are associated with increased resistance against S. Enteritidis cecal colonization in chickens. Therefore, providing a foundation for future studies to identify specific proteins within these pathways that are associated with resistance, which could provide breeders additional biomarkers to identify birds naturally more resistant to this important foodborne pathogen.